The "No Pants Subway Ride" and Discussions of Deviance - Kimpel, Jeanne (TRAILS: Teaching Resources and Innovations Library for Sociology, 2012)
The purpose of this exercise is to introduce the concept of deviance and create a fun-filled atmosphere in which to begin this discussion. This exercise facilitates a discussion on various concepts of deviance using short 5-6 minute clips from www.improveverywhere.com. The students will gain knowledge and understanding on the concepts of deviance, conformity, norms, folkways, mores, relativity of deviance, as well as ethics in research. At the end of this class session, the students are able to discuss and apply these concepts to specific situations.